EXTERNAL OFFAL WEIGHTS OF WHITE GOLD CROSSBRED CHICKEN WITH LANCY FED DRAGON FRUIT PEEL JUICE (Hylocereus Polyrhizus) THROUGH DRINKING WATER - N., Fitriana; Dewi, G. A. M. K.; Wijana, I W. (Jurnal Peternakan Tropika, 2020)
The purpose of the study is to knowing effect of giving peel dragon fruit juice to weight of offal external in chicken through water White Gold X Lancy . This research had been conducted chicken that in animal husbandry in Cekomaria Street, Banjar Kedua, Peguyangan Kangin, Denpasar City, Bali during 8 weeks. The design used a Completely Randomized Design (CRD) consisting of 4 treatments and 4 repeating and in every repeating consisted of 3 crossbred chickens White Gold X Lancy . The treatments are, R0: Without addition of dragon fruit peel juice through drinking water, R1: Addition of 5% dragon fruit peel juice through drinking water, R2: Addition 10% of dragon fruit peel juice through drinking water and R3: Addition of 15% of dragon fruit peel juice through drinking water. The observed variables were head weight, neck weight, leg weight, blood weight, and hair weight. The results showed that treatments R1, R2, and R3 had a higher weight  on the head, neck and legeach 4,71%, 4,21% and 8,83% than R0 significant different (P<0,05), but not significant different (P>0,05) weight on the bload and hair weight. Based on the result, it can be concluded that addition of dragon fruit peel as much as 5%, 10% and 15% affacted weight of head, neck and foot but not affected weight of blood and hair crossing chicken White Gold X Lancy aged 6-14 weeks. Keywords : Crossbred chicken, external offal , dragon fruit peel